Exploring HR Collaborative Initiatives in Opening Global Market Access for MSMEs - Nanik Wahyuningtiyas; Budi Eko Soetjipto (International Forum of Researchers and Lecturers, 2025)
The digital era has transformed marketing strategies, particularly for tech startups targeting Generation Z (Gen Z). This study investigates the influence of guerrilla and viral marketing on Gen Z consumer perceptions and behaviors in the context of tech startups, focusing on a risk-based entrepreneurial marketing approach. A quantitative survey with 212 Gen Z respondents was conducted to analyze the effects of these marketing strategies on consumer engagement, brand perception, and purchasing behavior. The results show that guerrilla and viral marketing significantly enhance consumer engagement and brand perception, but they do not directly influence Gen Z behavior or purchasing decisions. The findings highlight the importance of emotional engagement and brand authenticity in shaping consumer perceptions. This research fills a gap in understanding how resource-constrained tech startups can leverage risk-based marketing strategies to engage Gen Z, providing practical insights for designing effective campaigns. Future studies should explore additional factors like brand trust and values to bridge the gap between engagement and behavior